Plant-plant competition influences temporal dynamism of soil microbial enzyme activity - Schofield, E.J.; Brooker, R.W.; Rowntree, J.K.; Price, E.A.C.; Brearley, F.Q.; Paterson, E. (Soil biology & biochemistry, 2019)
Root-derived compounds can change rates of soil organic matter decomposition (rhizosphere priming effects) through microbial production of extracellular enzymes. Such soil priming can be affected by plant identity and soil nutrient status. However, the effect of plant-plant competition on the temporal dynamics of soil organic matter turnover processes is not well understood. This study used zymography to detect the spatial and temporal pattern of cellulase and leucine aminopeptidase activity, two enzyme classes involved in soil organic matter turnover. The effect of plant-plant competition on enzyme activity was examined using barley (Hordeum vulgare) plants grown in i) isolation, ii) intra- and iii) inter-cultivar competition. The enzyme activities of leucine aminopeptidase and cellulase were measured from portions of the root system at 18, 25 and 33 days after planting, both along the root axis and in the root associated area with detectable enzyme activity. The activities of cellulase and leucine aminopeptidase were both strongly associated with plant roots, and increased over time. An increase in the area of cellulase activity around roots was delayed when plants were in competition compared to in isolation. A similar response was found for leucine aminopeptidase activity, but only when in intra-cultivar competition, and not when in inter-cultivar competition. Therefore, plant-plant competition had a differential effect on enzyme classes, which was potentially mediated through root exudate composition. This study demonstrates the influence of plant-plant competition on soil microbial activity and provides a potential mechanism by which temporal dynamism in plant resource capture can be mediated. [Display omitted] •Soil enzyme activity was strongly associated with plant roots.•Root axis activity was not temporally dynamic when in plant-plant competition.•Root associated area was temporally dynamic in response to plant competition.•Peak cellulase activity was delayed when in competition compared to isolation.•Leucine aminopeptidase activity was delayed only in intra-cultivar competition.